The potential of nanoparticles in stem cell differentiation and further therapeutic applications. Issue 12 (31st October 2016) - Dayem, Ahmed Abdal; Choi, Hye Yeon; Yang, Gwang‐Mo; Kim, Kyeongseok; Saha, Subbroto Kumar; Kim, Jin‐Hoi; Cho, Ssang‐Goo
Abstract: Tissue regeneration could offer therapeutic advantages for individuals experiencing organ or tissue damage. Recently, advances in nanotechnology have provided various nanomaterials, with a wide range of applications, for modulating stem cell behavior and for further therapeutic applications in tissue regeneration. Defects in cell proliferation and differentiation, a low mechanical strength of scaffolds, and inefficient production of factors that are essential for stem cell differentiation are the current challenges in tissue regeneration. This review provides a brief explanation about the link between nanotechnology and tissue engineering, highlighting the current literature about the interaction between nanoparticles (NPs) and stem cells, the promotional effect of NPs on stem cell differentiation into various lineages, and their possible therapeutic applications. We also tried to describe the mechanism through which NPs regulate the spatial‐temporal release and kinetics of vital growth and differentiation factors, enhance stem cell differentiation, and improve culture conditions for in vivo tissue regeneration. The field of nanotechnology is promising and provides novel nanomaterials and methods with valuable clinical applications in the regenerative medicine. Understanding the mechanism, as well as the toxic effects of NPs in stem cell biology will undoubtedly provide valuable insight into their clinical application in the regenerative medicine. Abstract : Nanotechnology possesses various medical applications. In this review, the authors describe the role of the nanomaterials in the differentiation of several types of stem cells to osteogenic, chondrogenic, adipogenic, neuronal, and other lineages. These nanomaterials can alone enhance the differentiation or promote the effect of the other differentiation factors. This review afford the possible application of nanoparticles (NPs) as tailored therapies for the regeneration of severely damaged tissues via the modulation of stem cell differentiation.